Coronary tortuosity is negatively correlated with coronary atherosclerosis. Issue 12 (December 2018) - Li, Yang; Feng, Yi; Ma, Genshan; Shen, Chengxing; Liu, Naifeng
Objective: The impact of coronary tortuosity on coronary atherosclerosis remains unclear. This study was performed to determine to the relationship between coronary tortuosity and the presence of coronary atherosclerosis. Methods: Tortuosity and the presence of coronary atherosclerosis in the main coronary arteries were evaluated. The coronary artery was divided into non-tortuous and tortuous segments. The incidence of coronary atherosclerosis between the two segments was compared. Results: The prevalence of coronary atherosclerotic stenosis was significantly lower in the tortuous than non-tortuous segment. Conclusion: The prevalence of coronary atherosclerotic stenosis is lower in the coronary tortuous than non-tortuous segment, indicating that coronary tortuosity might be considered a protective factor for atherosclerosis.